Budaya Pop dan Transformasi Identitas Muslim: Pendekatan Kualitatif - Syafira Azzahra (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
In the era of globalization, pop culture has become a powerful medium in shaping individual identities, including Muslim identity. This article explores how pop culture influences the transformation of Muslim identity within the context of globalization, particularly among the younger generation. Through a qualitative approach, this research delves into the interaction between elements of popular culture, such as music, film, and social media, with religious practices and values within Islam. The study utilizes in-depth interviews and content analysis from various media platforms, including social media and other media sources, to understand the dynamics of identity change among Muslim youth. The findings will illustrate how pop culture shapes the perspectives and behaviors of the Muslim generation, blending Islamic traditions with elements of modernity to form a unique Muslim identity. This article provides insight into how Muslim identity in the modern era continues to evolve and adapt within an increasingly connected and diverse society. The research makes a significant contribution to our understanding of Muslim identity in the modern age, highlighting the complexity and fluidity of identity in a constantly changing society. This article makes a crucial contribution to cultural and religious studies and paves the way for further research on this topic. It emphasizes the importance of understanding Muslim identity as a dynamic and layered phenomenon that continuously evolves with global culture. This study offers new insights into the transformation of Muslim identity in modern society and underscores the importance of understanding the influence of pop culture on the identity transformation process. Thus, this article contributes to a broader discussion on identity, religion, and culture in the context of globalization.